The nutritional, microbiological, and bioactive potential of dangke fermented food as a functional food in Indonesia: A literature review - Anggoro La Angka; Aryanti R Bamahry; Dian Fahmi Utami; Yani Sodiqah; Abdul Mubdi Ardiansar Arifuddin Karim (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Dangke is a traditional fermented dairy product from South Sulawesi, Indonesia, with considerable potential to be developed as a functional food based on local wisdom. Beyond its role as a source of animal protein, dangke contains lactic acid bacteria and bioactive compounds that may confer health benefits. However, scientific evidence regarding its nutritional value, microbiological characteristics, and bioactive potential remains fragmented and has not been systematically synthesized. Purpose: To identify, synthesize, and critically evaluate various research results related to nutritional composition, microbiological safety, and potential of bioactive compounds in dangke. Method: This study employed a literature review design by analyzing national and international scientific articles published between 2015 and 2025. Literature searches were conducted using PubMed, Google Scholar, ScienceDirect, and ResearchGate databases. Eligible articles were analyzed narratively through summarizing, synthesizing, comparing, and critically appraising processes to evaluate the nutritional composition, microbiological properties, and bioactive potential of dangke. Results: A total of 10 relevant studies were included. The findings indicate that dangke contains relatively high protein levels (approximately 14–18%), fat, and essential micronutrients such as vitamin A, vitamin C, zinc, and selenium. Microbiologically, dangke is predominantly composed of lactic acid bacteria, particularly Lactobacillus plantarum and Lactobacillus fermentum, which exhibit probiotic potential. Fermentation processes produce bioactive peptides associated with antihypercholesterolemic, antihyperglycemic, anti-obesity, antimicrobial, and immunomodulatory effects, primarily supported by experimental animal studies. Conclusion: Based on available scientific evidence, dangke demonstrates a combination of nutritional value, beneficial microbiological activity, and bioactive potential that supports its role as an Indonesian functional food. Nevertheless, broader application requires standardized production methods, improved food safety practices, and further human clinical studies to strengthen the level of evidence.